INNOVATION OF AN APPLICATION BASED INDEPENDENT VILLAGE INFORMATION SYSTEM (SI EMAN) IN THE DEVELOPMENT OF E-GOVERNMENT IN KETIMANG VILLAGE - Wahyuningsih, Yiyin Antias; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze and describe the innovation of the application-based Independent Village Information System (Si Eman) in supporting the development of e-government in Ketimang Village. The research focuses on evaluating the system's effectiveness in improving administrative processes and public service delivery at the village level. Method: The research uses a descriptive qualitative approach. Data were collected through in-depth interviews with village officials, direct observations of system usage, and documentation review. Both primary and secondary data sources were utilized to ensure comprehensive insights. Results: The findings reveal that the Si Eman application has several innovative attributes. First, it offers a relative advantage by simplifying data management and reducing the risk of data loss. Second, its compatibility with existing village needs and work processes facilitates easier adoption. Third, complexity is still a challenge due to limited digital literacy among staff and occasional technical issues. Fourth, observability is enhanced through regular training programs that improve user understanding and encourage system utilization. Novelty: The study contributes to the literature on rural e-government by showcasing how a locally developed application like Si Eman can effectively bridge digital gaps in village administration. It highlights the importance of context-specific innovations that are aligned with local capacities and emphasizes the role of digital training in ensuring successful implementation.